Awareness of Sport Massage Therapy among University Level Football Players in Pakistan - Muhammad Zeeshan Butt; Syed Muhammad Bilal Gillani; Basit Ali (The Sky)
Sports massage is very common among the athletes of developed nations. Since many of studies have been conducted and revealed positive benefits of Sports massage (SMT). The results of different studies show that it improves health, enhance immunity, speedy recovery after an injury, and after intensive training. This study is aimed to investigate the knowledge of university level athletes in Pakistan about the concept of Sport Massage Therapy (SMT). 125 participants were participated in this study, the sample was selected using convenient sampling technique and data was gathered using sport massage questionnaire developed by Lloyd Leach and Mignon Schilz. The results show that there is very little awareness and knowledge about Sport Massage Therapy among the University Football Players. The results of this study also indicate athletes perceive that sport massage helpful in rehabilitation and just an event of enjoyment. It was concluded on basis of results that athlete have very little knowledge about the role of sport massage in Sport Performance.